The scholarly communication office as a perspective of action for university libraries - Silva, Eduardo Graziosi [UNESP]; Guimarães, José Augusto Chaves [UNESP] (Ibersid, 2023)
Considering the current challenges faced by universities, such as the duty to be accountable to society, the need for greater scientific visibility, high competitiveness based on international rankings, and the advancement of Information and Communication Technologies, the figure of the scholarly communication office is analyzed within the scope of the university library. To do so, existing scientific communication models are analyzed to arrive at products and services from a scholarly communication office based on a sample of fifteen existing scholarly communication offices in libraries of universities considered excellent in four international university rankings. The results show, at different stages of development, activities related to open access, copyright, research data management, author identifiers, research impact, metrics, publication, and repositories. It is concluded that the identification and systematization of initiatives related to support services for scientific communication located in libraries, for the purpose of structuring offices of this nature based on the studied reality, lead us to think about the need for librarian training to include a solid foundation in scientific communication (with a strong basis in the sociology of science), not only from a normative point of view, but also from an effectively investigative experience that allows the librarian to put themselves in the position of the researcher and thus have clarity on the aspects that require their support.
Las oficinas de comunicación científicas: perspectivas de actuación para las bibliotecas universitarias
O escritório de comunicação científica como perspectiva de atuação para bibliotecas universitárias
Keywords: Scholarly communication; Scholarly communication offices; University libraries